Oral health follow-up studies in the 1993 Pelotas (Brazil) birth cohort study: methodology and principal results Estudos de saúde bucal na coorte de nascimentos de Pelotas, Rio Grande do Sul, Brasil, 1993: metodologia e resultados principais - Marco A. Peres; Aluísio Jardim Barros; Karen Glazer Peres; Cora Luiza Araújo; Ana M. B. Menezes; Pedro C. Hallal; Cesar G. Victora (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
The aim of this study was to describe oral health follow-up studies nested in a birth cohort. A population-based birth cohort was launched in 1993 in Pelotas, Rio Grande do Sul State, Brazil. Two oral health follow-up studies were conducted at six (n = 359) and 12 (n = 339) years of age. A high response rate was observed at 12 years of age; 94.4% of the children examined at six years of age were restudied in 2005. The mean DMF-T index at age 12 was 1.2 (SD = 1.6) for the entire sample, ranging from 0.6 (SD = 1.1) for children that were caries-free at age six, 1.3 (SD = 1.5) for those with 1-3 carious teeth at six years, and 1.8 (SD = 1.8) for those with 4-19 carious teeth at six years (p < 0.01). The number of individuals with severe malocclusions at 12 years was proportional to the number of malocclusions at six years. Oral health problems in early adolescence were more prevalent in individuals with dental problems at six years of age. O objetivo deste trabalho foi descrever estudos de saúde bucal em uma coorte de nascimentos. Em 1993, teve início uma coorte de nascimentos de base populacional em Pelotas, Rio Grande do Sul, Brasil. Dois estudos de saúde bucal aos 6 (n = 359) e 12 anos de idade (n = 339) foram realizados. Foi observada uma alta taxa de resposta no período entre 6 e 12 anos de idade; 94,4% das crianças pesquisadas em 1999 foram examinadas em 2005. A média do índice CPO-D aos 12 anos foi de 1,2 (DP = 1,6) para a população como um todo, variando de 0,6 (DP = 1,1) para o grupo livre de cáries aos 6 anos, 1,3 (DP = 1,5) para os que apresentaram 1-3 dentes atacados pela cárie e 1,8 (DP = 1,8) para aqueles com 4-19 dentes atacados pela cárie (p < 0,01). Observou-se um aumento da proporção de indivíduos com oclusopatias muito severas aos 12 anos, conforme o número de oclusopatias presentes aos 6 anos de idade. Problemas bucais no início da adolescência foram mais prevalentes nos indivíduos que apresentaram agravos à saúde bucal na infância.